If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4g + 9 = -4g + 9g Reorder the terms: 9 + -4g = -4g + 9g Combine like terms: -4g + 9g = 5g 9 + -4g = 5g Solving 9 + -4g = 5g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-5g' to each side of the equation. 9 + -4g + -5g = 5g + -5g Combine like terms: -4g + -5g = -9g 9 + -9g = 5g + -5g Combine like terms: 5g + -5g = 0 9 + -9g = 0 Add '-9' to each side of the equation. 9 + -9 + -9g = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -9g = 0 + -9 -9g = 0 + -9 Combine like terms: 0 + -9 = -9 -9g = -9 Divide each side by '-9'. g = 1 Simplifying g = 1
| XY+5x-3y-7x+2xy-4z= | | 5x-3x=13-7 | | 4(x-3)+1+2+3=0 | | 22-14=4(x-8) | | 6-9(x+2+3)=0 | | 6a+14= | | 3(3x+2)+4(x+2)=0 | | 20b^2c-17bc-63c= | | X^2-14+33=0 | | 25v^2+19v+4= | | -7a-2y+7+2y+5a= | | 4x+20=x+32 | | 5x^2-22x-15= | | 4x^4+9x^3-2x+7=0 | | (7+w)(2w-9)=0 | | 4x^2-14=0 | | 6x-36+4=8x+16-10 | | 3(x+2)+5x-(x-1)=-2x+1 | | 4a^2-7a-28a+49= | | 2m= | | 4x^4+9x^3-2x+7=1482 | | 4x^4+9x^3-2x+7=27 | | -5g+20=-7g+7g | | -10(x+5)+76=-12-12 | | 4x^4+9x^3-2x+7=12 | | 3r^2-10r+8= | | 8x^2-2xy-y^2=0 | | 4a^2+9a-28= | | 6a+17+7=0 | | m+5= | | 12a^2+14a-11a^2= | | 12c^2d-13cd-35d= |